Synergistic advancements in sewage-driven microbial fuel cells: novel carbon nanotube cathodes and biomass-derived anodes for efficient renewable energy generation and wastewater treatment - Barakat, Nasser A. M.; Gamal, Shimaa; Kim, Hak Yong; Abd El-Salam, Nasser M.; Fouad, Hassan; Fadali, Olfat A.; Moustafa, Hager M.; Abdelraheem, Omina H. (Frontiers in Chemistry, 2023)
Microbial fuel cells (MFCs) offer a dual solution of generating electrical energy from organic pollutants-laden wastewater while treating it. This study focuses on enhancing MFC performance through innovative electrode design. Three-dimensional (3D) anodes, created from corncobs and mango seeds via controlled graphitization, achieved remarkable power densities. The newly developed electrode configurations were evaluated within sewage wastewater-driven MFCs without the introduction of external microorganisms or prior treatment of the wastewater. At 1,000°C and 1,100°C graphitization temperatures, corncob and mango seed anodes produced 1,963 and 2,171 mW/m2, respectively, nearly 20 times higher than conventional carbon cloth and paper anodes. An advanced cathode composed of an activated carbon-carbon nanotube composite was introduced, rivaling expensive platinum-based cathodes. By optimizing the thermal treatment temperature and carbon nanotube content of the proposed cathode, comparable or superior performance to standard Pt/C commercial cathodes was achieved. Specifically, MFCs assembled with corncob anode with the proposed and standard Pt/C cathodes reached power densities of 1,963.1 and 2,178.6 mW/m2, respectively. Similarly, when utilizing graphitized mango seeds at 1,100°C, power densities of 2,171 and 2,151 mW/m2 were achieved for the new and standard cathodes, respectively. Furthermore, in continuous operation with a flow rate of 2 L/h, impressive chemical oxygen demand (COD) removal rates of 77% and 85% were achieved with corncob and mango seed anodes, respectively. This work highlights the significance of electrode design for enhancing MFC efficiency in electricity generation and wastewater treatment.